2020
DOI: 10.9734/jpri/2020/v32i3731006
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Conventional 2.0 mm Miniplates versus 3-D Plates In Management of Mandibular Fractures

Abstract: Objective: To compare the outcomes stability, malunion and intra operative time by using 2.0mm conventional miniplates and 3-D plates in management of the anterior mandibular fracture. Materials and Methods: Total 94 patients were included and equally divided in two groups. Fixation of fracture was done by 2.0mm conventional miniplates in Group-A and a single 3D plate in Group-B. Stability, healing and malunion were assessed on follow-up at 1st week, 6th week, and 12th week using Chi Square Test. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…24.5 years. In Kumari et al study [21] the mean age of patients in group A and group B was 31.38±9.03 years and 30.10±9.35 years, respectively".…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…24.5 years. In Kumari et al study [21] the mean age of patients in group A and group B was 31.38±9.03 years and 30.10±9.35 years, respectively".…”
Section: Discussionmentioning
confidence: 93%
“…According to the studies by Zafar KJ [18], Kumar [23], Kinra [24], and El Nakeeb [22], they also reported "decreased operating with 3-D plates as compared to 2mm conventional miniplates for the fixation of anterior mandibular fracture". In Kumari et al study [21], "the operating time needed in group A (Conventional 2mm miniplate) was < 30minutes in 22(46.8) cases and >30 minutes in 25(53.2%) cases, while in group B all 47 (100%) cases were found with intraoperative time<30 minutes".…”
Section: Discussionmentioning
confidence: 97%